2007
DOI: 10.1007/s12011-007-8013-7
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Factors Controlling Essential Hypertension—a Study in the Chandigarh, India Population

Abstract: Essential hypertension (EH) is a major public health problem world over and in India. Recent data on EH in the population of Chandigarh (Union Territory and capital of Punjab and Haryana States of India) revealed that the prevalence of EH has become double in the last 30 years in the residents of Chandigarh (26.9 to 45.80% in the year 1968 and 2002). Zinc (Zn), copper (Cu), magnesium (Mg), and manganese (Mn) in the serum are considered important in maintaining the human hypertension. The high Zn intake was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 52 publications
(67 reference statements)
2
32
1
3
Order By: Relevance
“…Among the different metal ions, it seems that Zn is an important metal ion which plays a role in the pathogenesis of essential HT [39]. In interesting studies carried out in HTS patients by Anaelechi et al [40] a nd Taneja and Mandal [41], it has been revealed that serum Zn levels was found to be increased in HTS patients as compared to normal subjects while other metals were decreased or not statistically different. They further reported that this condition seemed to increase progressively from prehypertensives to those with stage-II HT.…”
Section: Disparity In Blood Metals (Mg Zn Cu Mn) Status Is Linked mentioning
confidence: 99%
“…Among the different metal ions, it seems that Zn is an important metal ion which plays a role in the pathogenesis of essential HT [39]. In interesting studies carried out in HTS patients by Anaelechi et al [40] a nd Taneja and Mandal [41], it has been revealed that serum Zn levels was found to be increased in HTS patients as compared to normal subjects while other metals were decreased or not statistically different. They further reported that this condition seemed to increase progressively from prehypertensives to those with stage-II HT.…”
Section: Disparity In Blood Metals (Mg Zn Cu Mn) Status Is Linked mentioning
confidence: 99%
“…Roles of major minerals or trace elements in the etiology of hypertension formation have been worldwide studied (Ekmekci et al, 2003;Taneja and Mandal, 2007). Some of them act as nutrients to prevent hypertension independently or with interaction effects between them (Taneja and Mandal, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Some of them act as nutrients to prevent hypertension independently or with interaction effects between them (Taneja and Mandal, 2007). Alkaline-earth elements (AEEs), especially calcium (Ca) and magnesium (Mg), had been suggested to involve into blood pressure regulation or hypertension formation in human body (Sacks et al, 1995;Ekmekci et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…5 Imbalances of zinc, copper, magnesium and manganese affect blood pressure and are associated with hypertension. 6 Medical physiology studies have indicated correlations between the microelement content of body tissues and metabolism. 7 Trace elements have been implicated in the etiology of CVD, 8,9 with several examples showing the multi-level impact of trace elements on arterial blood pressure.…”
Section: Introductionmentioning
confidence: 99%